2018
DOI: 10.17576/jsm-2018-4701-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Cardiovascular Risk in Chronic Kidney Disease Patients: A Biomarker Approach

Abstract: Cardiovascular disease (CVD) is a major cause of morbidity and mortality in chronic kidney disease (CKD) patients. This study aimed to determine the roles of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Also, triglyceride levels in non-CVD patients were significantly higher than those of CVD patients with a p-value of (0.002). This result agreed with a previous research study performed in Malaysia in 2018 and showed that triglycerides were elevated in non-CVD patients [ 5 ]. This could be explained as individuals with CVD have more control over triglycerides levels than non-CVD patients as they are on medications.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Also, triglyceride levels in non-CVD patients were significantly higher than those of CVD patients with a p-value of (0.002). This result agreed with a previous research study performed in Malaysia in 2018 and showed that triglycerides were elevated in non-CVD patients [ 5 ]. This could be explained as individuals with CVD have more control over triglycerides levels than non-CVD patients as they are on medications.…”
Section: Discussionsupporting
confidence: 93%
“…In this patient population, dying from CVD is exponentially greater than the patient reaching end-stage renal disease [ 4 ]. It is a belief that CKD is a cardiovascular disease equivalent [ 5 ]. Additionally, there could be risk factors that are common between CKD and CVD, such as Diabetes and Hypertension [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health-related quality of life is a strong predictor of death and hospitalization, which may influence the prognosis and course of the illness. This decline in quality of life in dialysis patients is a result of death anxiety ( Abdul Gafor et al, 2018 ). Another factor contributing to the current sample’s low quality of life may be their old age, low socioeconomic level, and lack of education and unemployment ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%